Depression and social capital in people living with HIV. Issue 1 (18th August 2019) - Perazzo, Joseph D.; Currie, Jackson; Horvat Davey, Christine; Lambert, Joshua; Webel, Allison R.
Accessible summary: What is known on the subject?: Depression affects 1 in 20 Americans, and people living with HIV experience depression at 2–3 times the rate of the general population. Recent research has shown that a person's level of social connectedness (e.g., social networks) is important to understanding their health and ability to get help when they need it. The scientific rationale of this work is to determine whether there is a direct relationship between levels of depression and a measure of social connectedness in people with HIV who are at higher than normal risk of depression and depressive symptoms. What this paper adds to existing knowledge?: We examined the relationship between levels of depression and social capital in people living with HIV to determine whether depression may influence their beliefs about their social connectedness and available resources. We found that as depression increases, self‐reported social capital decreases, suggesting that people living with HIV who are depressed may feel less socially connected and/or not be confident they can access resources when they need them. What are the implications for practice: Mental health nurses are particularly well‐positioned to help people living with HIV who are living with depression by helping them build skills for building and maintaining relationships, adhering to co‐administered HIV and mental health medical treatments, and helping these individuals to identify and address barriers to social connectedness. Helping people living with HIV to address depression and promoting social connectedness can not only improve quality of life, but have major long‐term health benefits. Abstract: Introduction: People living with HIV (PLWH) are disproportionately burdened by depression, with estimates as high as 80% of PLWH reporting depressive symptoms. Depression in PLWH is complex, and has been linked with biological and psychosocial causes, including low social capital. Few studies have examined the relationship between social capital and depression in PLWH. Aim/Question: We conducted a secondary analysis of the relationship between social capital (Social Capital Scale score) and depression (Beck Depression Inventory‐II scores) to determine whether depression predicted levels of social capital in a sample of 108 PLWH. Results: Depression was significantly associated with lower social capital r (105)  =  −.465 p  < .001. Depression remained a significant predictor of social capital in the linear regression model, F (5, 101) = 8.508, p  < .000, R 2   =  0.296, when controlling for age and education level. Discussion: Our results suggest that depression may be a significant predictor of low social capital, and these factors may have cyclical relationships that explain persistent depression in this population. Implications for practice: Mental health nurses are particularly well‐positioned to help PLWH who are living with depression by helping them build skills for building and maintaining relationships, adhering to co‐administered HIV and mental health medical treatments, and helping these individuals to identify and address barriers to social connectedness.